The lipid composition of extracellular vesicles: applications in diagnostics and therapeutic delivery - Ghadami, Samaneh; Dellinger, Kristen (Frontiers in Molecular Biosciences, 2023)
Extracellular vesicles (EVs), including exosomes, with nanoscale sizes, biological origins, various functions, and unique lipid and protein compositions have been introduced as versatile tools for diagnostic and therapeutic medical applications. Numerous studies have reported the importance of the lipid composition of EVs and its influence on their mechanism of action. For example, changes in the lipidomic profile of EVs have been shown to influence the progression of various diseases, including ovarian malignancies and prostate cancer. In this review, we endeavored to examine differences in the lipid content of EV membranes derived from different cell types to characterize their capabilities as diagnostic tools and treatments for diseases like cancer and Alzheimer's disease. We additionally discuss designing functionalized vesicles, whether synthetically by hybrid methods or by changing the lipid composition of natural extracellular vesicles. Lastly, we provide an overview of current and potential biomedical applications and perspectives on the future of this growing field.